Making Indonesia as Integrated Halal Zone and World Halal Sector Hub Through the Implementation of Halal Supply Chain - Zulfikar Hasan (Journal of Islamic Economic and Business Research, 2021)
Halal supply chain management is one of the implementations that has been undertaken by several countries in the world, and even countries with a majority non-Muslim population. The halal sector in the world has developed quite rapidly. It has penetrated to all fields, one of which is Islamic banking and finance which has evolved quite well in helping the economy of a country. The research used in this research is descriptive qualitative research as an illustration in the Halal Supply Chain process that has been used by several states that have successfully implemented this system. Halal Supply Chain is a cycle that has been set by each country and has standards that guide the processing of a product, so it reaches the consumer. Indonesia is determined to become the centre of the halal world through the implementation of the halal supply chain in the form of Integrated Halal Zone (IHZ), IHZ is one of the functions to encourage the halal industry to develop and be able to compete with other countries quickly. Additionally, the Indonesian Ulema Council and the Ministry of Religion can easily oversee halal product standards from upstream to downstream. Hopefully the results of this research will contribute to the academic world and practitioners of Islamic economics.